Uso de biocarvão e suas biomassas precursoras para remediação de hidrocarbonetos policíclicos aromáticos em água - Jesus, Jany Hellen Ferreira de (2016)
The increasing demand for fresh water has stimulated interest in new adsorbent materials suitable for use in the remediation of contaminated waters. This work evaluates different biomasses and their biochar for use as adsorbents for the removal of polycyclic aromatic hydrocarbons from water. Biochar (BBC and BCL) were obtained by the pyrolysis of coconut bagasse (BC) and orange peel (CL). The use of infrared spectroscopy analysis revealed that some of the functional groups of the biomasses were retained after pyrolysis at 350 °C. The heat treatment resulted in greater surface area, pore size, and pore volume of the biochar, compared to the precursor biomasses, as confirmed by scanning electron microscopy. Thermogravimetric analysis showed that the biochar presented higher thermal stability than the original biomasses. X-ray diffraction analysis identified the presence of potassium chloride in BC and BBC, while elemental analysis revealed increased aromaticity of the biochar, reflected in smaller H/C ratios. Adsorption assays were performed to evaluate the effects of contact time and initial concentration for the removal of benzo(a)anthracene, benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(a)pyrene, and dibenzo(a,h)anthracene, individually and in a mixed solution. Identification and quantification of the compounds employed high performance liquid chromatography with fluorescence detection. The adsorption assays showed that there were no substantial differences in the amounts of the PAHs adsorbed by BC and BBC, while a increase was found for BCL, compared to CL. It was also verified that there was no competition between the PAHs for the adsorption sites of the materials. The adsorption could be best described by pseudo-second order kinetics and the Freundlich adsorption model. The adsorption mechanism probably involved π-π interactions of similar groups of the adsorbate and adsorbent, together with hydrophobic effects. The PAH could be desorbed from the adsorbents using ultrasonic extraction, and two further reuse cycles were tested. The proposed method provided efficient adsorption using a real sample, with removal rates from 86.29 to 8.12% (BC), 90.94 to 86.99% (BBC), 76.36 to 32.18% (CL), and 85.32 to 40.12% (BCL). The findings demonstrated the potential of these adsorbents for use in the removal of PAH from water.